Empowering Nigerian Youths through Technical Vocational Education and Training for Enhancing National Security - Chinedu, Caleb Chidozie; Oladiran, Stephen Olabiyi (Journal of Technical Education and Training, 2015)
The Nigerian government had initiated several youth empowerment programmes through TVET, but a lot of these programmes lack structure and their impact not felt by the nation’s youths. This is evident in the substantial number of youth that still lack work skills-which often results to unemployment, insecurity, loss of lives and properties and chaos. The study therefore, sought to investigate, TVET empowerment skills required by youths as a means for enhancing national security. Descriptive survey research design was used and data was obtained using a structured questionnaire known as the Empowerment Skill Inventory Checklist (ESIC). Eighty five TVET lecturers in post-secondary vocational institutions took part in the study. Findings revealed that youths require vocational skills in areas such as horticulture, business, engineering and construction works. Also recommended techniques and strategies for career development that include specific skills such as business skills, financial management skills, basic computation skills, communication skills and adaptation skills.